Bone Morphogenetic Protein 2 Is Involved in Oocyte Maturation Through an Autocrine/Paracrine Pathway in Scylla paramamosain - Yang, Yanan; Zhang, Peng; Cui, Zhaoxia; Bao, Chenchang (Frontiers in Marine Science, 2021)
Ovary-secreted autocrine/paracrine factors play important roles in regulating oocyte maturation via the autocrine/paracrine pathway. This study aimed to evaluate the functions of bone morphogenetic protein 2 (BMP2) in oocyte maturation and communication between follicle cells and oocytes. In our study, we first identified BMP2 from the mud crab Scylla paramamosain. Quantitative real-time PCR showed that BMP2 was detected in diverse tissues, notably in the ovary, stomach and gill. The expression levels of BMP2 transcripts increased during vitellogenesis. Spatial expression of BMP2 and receptors in the ovary revealed that BMP2 was exclusively detected in oocytes, whereas the receptors were expressed in both follicle cells and oocytes. RNAi tests revealed that the expression of cyclin B first decreased at 2 h and then increased at 4 h after BMP2 knockdown. These combined findings suggest that BMP2 may promote oocyte maturation through an autocrine/paracrine pathway in S. paramamosain.